Study on the molecular structure of epoxy resin without hardener in mortar - Nur Farhayu, Ariffin; Nor Hasanah, Abdul Shukor Lim; Sharifah Maszura, Syed Mohsin; Mohd Warid, Hussin; Abdul Rahman, Mohd Sam; Lee, Han Seung (IOP Publishing, 2020)
The principal of molecular structure of cement mortar is important as it shows a component and interaction between cement and additive. By using a themogrativimetric analysis, the phase of mortar structure when exposed to high temperature can be determined. This paper presents the study on influence of epoxy resin without hardener on the microstructure of mortar. Mortar specimens were prepared with mass ratio of 1:3 (cement: fine aggregate), water-cement ratio of 0.48 and 5 to 20% epoxy resin of cement content. All tested specimens were subjected to wet-dry curing; where compressive strength, apparent porosity, thermogrativimetric analysis and fourier transformation infrared spectroscopy were measure. Result shows that, all strength properties of epoxy mortar were significantly higher than control sample and became constant at 10 % of epoxy resin ratio. Thermogrativimetric analysis shows the weight loss of epoxy mortar was almost similar for various percentage of epoxy resin while from fourier transformation infrared spectroscopy test, the component of epoxy mortar and normal mortar was significantly different.